2018
DOI: 10.1371/journal.pone.0194231
|View full text |Cite
|
Sign up to set email alerts
|

Women’s preferences for alternative financial incentive schemes for breastfeeding: A discrete choice experiment

Abstract: BackgroundIncreasing breastfeeding rates have been associated with reductions in disease in babies and mothers as well as in related costs. ‘Nourishing Start for Health (NoSH)’, a financial incentive scheme has been proposed as a potentially effective way to increase both the number of mothers breastfeeding and duration of breastfeeding.AimsTo establish women’s relative preferences for different aspects of a financial incentive scheme for breastfeeding and to identify importance of scheme characteristics on pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 33 publications
0
18
0
1
Order By: Relevance
“…The DCE method has been used to guide the design of health programmes, including maternal and child health, by understanding the strength of user preferences for programme design features. [19][20][21][22][23][24] The DCE is a quantitative method that is useful for assessing the potential impact of strategies or programmes that have not been implemented, and understanding the relative value of, and trade-offs between, the programme attributes. It is based on what people say they will do that is, their stated preferences.…”
Section: Methodsmentioning
confidence: 99%
“…The DCE method has been used to guide the design of health programmes, including maternal and child health, by understanding the strength of user preferences for programme design features. [19][20][21][22][23][24] The DCE is a quantitative method that is useful for assessing the potential impact of strategies or programmes that have not been implemented, and understanding the relative value of, and trade-offs between, the programme attributes. It is based on what people say they will do that is, their stated preferences.…”
Section: Methodsmentioning
confidence: 99%
“…However, the proposed MCT approach would require, among other things, sound monitoring to ensure that breastfeeding actually took place, consistency in the best timing of delivery of cash distribution and breastfeeding counselling visits, recognizing that many mothers receiving the cash transfer face major social determinants of health challenges. These need to be addressed through supportive social protection, efficacy evaluation of the intervention, and economic policies [41,42,[68][69][70].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the few studies available have analyzed cash transfers targeting several outcomes (e.g. education and health) and not specifically paid maternity leave, in spite that some of these studies have shown that cash transfer may have positive impact on breastfeeding outcomes [39][40][41][42][43][44]. This study is the first to provide such cost estimates for Indonesia, and as such can provide urgently needed evidence for policy making purposes in the context of supporting recommended breastfeeding practices, especially given the relatively low health budget in Indonesia (under 5% share of GDP as of 2014) [45].…”
Section: Introductionmentioning
confidence: 99%
“…Becker, 2018 [79] "Respondents had read, understood and engaged constructively with the choice task"…”
Section: Applied Dces Including a Test Of Understanding Within The DCmentioning
confidence: 99%